Λ and Σ0 pair production in two-photon collisions at LEP - Dova, María Teresa (2002)
Strange baryon pair production in two-photon collisions is studied with the L3 detector at LEP. The analysis is based on data collected at e+e− centre-of-mass energies from 91 GeV to 208 GeV, corresponding to an integrated luminosity of 844 pb−1. The processes γ γ → ̄ and γ γ → 00 are identified. Their cross sections as a function of the γ γ centre-of-mass energy are measured and results are compared to predictions of the quark–diquark model.